Kedudukan Pembiayaan Bank Syariah pada Kapasitas Masyarakat di Era Digital Fathia Zuhra Nasution - Fathia Zuhra Nasution (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
The study examined the position of Islamic bank financing in community capacity. Islamic Banking can be positioned by advancing the prosperity of the community. With the purpose of intermediation, Islamic Banking can add up money and disclose to the population in the form of financing to be productive. The study of this study is to understand the interaction with Islamic banking financing for people's capacity in the digital era and the influence of Islamic banking financing on trade in our country in the age of digitalization. The study uses a descriptive qualitative system and literature review with expert books first. This study examines how Islamic banking is positioned in advancing economic activities and employment. Islamic bank financing can be well positioned to advance the treatment economy in various regions.